A Systematic Review and Meta-Analysis of Acupuncture Treatment for Oral Ulcer. (8th November 2022) - Yan, Hang; Chen, Tianxi; Zuo, Yuling; Tu, Yang; Ai, Huangping; Lin, Yuqi; Chen, Yongcan
Abstract : Background . Oral ulcer (OU) is a common oral mucosal disease manifested with obvious pain. In some studies, the efficacy of acupuncture in OU has been confirmed, but systematic reviews and meta-analyses for them are lacking. Our aim is to evaluate the efficacy of acupuncture in the treatment of OU. Methods . We searched the literature from eight databases from their inception to December 2021. We included randomized controlled trials of acupuncture for the treatment of oral ulcer. The meta-analysis was carried out using Review Manager 5.3 and Stata 16.0. The main outcomes were the effective rate and the recurrence rate, the secondary outcomes were the visual analogue score (VAS) and the ulcer healing time. Results . Totally, 18 studies were finally included in the meta-analysis, including 1, 422 patients. In meta-analyses, we found that in comparison with Western medicine, acupuncture can improve effective rate (OR = 5.40, 95% CI: 3.40 to 8.58), reduce the ulcer recurrence rate (OR = 0.21, 95% CI: 0.13 to 0.33), and relieve the ulcer pain (MD = −2.26, 95% CI: −4.27to−0.24). In addition, compared with Western medicine, acupuncture plus Western medicine also can improve effective rate (OR = 2.95, 95% CI: 1.48 to 5.85). Compared with the Chinese medicine, the acupuncture plus Chinese medicine can improve the effective rate (OR = 8.26, 95% CI: 3.61 to 18.88) and relieve the ulcer pain (MD = −1.85, 95% CI: −2.51 to −1.19). Conclusion . Acupuncture may be more effective than Western medicine in terms of efficacy rate, and acupuncture combined with Western or Chinese medicine may have the potential to reduce the recurrence of ulcer and relieve the ulcer pain. However, due to limited evidence, higher quality and more rigorously designed clinical trials with larger sample sizes will be needed to further confirm our findings.